2020
DOI: 10.3389/fphys.2020.00722
|View full text |Cite
|
Sign up to set email alerts
|

The Dark Side of Nrf2 in the Heart

Abstract: Nuclear factor-erythroid factor 2-related factor 2 (Nrf2) is a critical transcription factor that regulates the expression of over 1000 genes in the cell under normal and stressed conditions. These transcripts can be categorized into different groups with distinct functions, including antioxidative defense, detoxification, inflammatory responses, transcription factors, proteasomal and autophagic degradation, and metabolism. Nevertheless, Nrf2 has been historically considered as a crucial regulator of antioxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 46 publications
1
69
0
Order By: Relevance
“…Nrf2 has been considered as a hermetic factor ( Maher and Yamamoto, 2010 ). However, such a theory that either too much or too little of Nrf2 can lead to pathological endpoints cannot explain Nrf2-mediated cardiac phenotypes ( Zang et al, 2020a ). For example, CR-Nrf2 Tg mice is perfectly normal under physiological conditions, and sustained PO does not result in super-activation of Nrf2 in the heart although Nrf2 activation promotes the PO-induced cardiomyopathy ( Zang et al, 2020a ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nrf2 has been considered as a hermetic factor ( Maher and Yamamoto, 2010 ). However, such a theory that either too much or too little of Nrf2 can lead to pathological endpoints cannot explain Nrf2-mediated cardiac phenotypes ( Zang et al, 2020a ). For example, CR-Nrf2 Tg mice is perfectly normal under physiological conditions, and sustained PO does not result in super-activation of Nrf2 in the heart although Nrf2 activation promotes the PO-induced cardiomyopathy ( Zang et al, 2020a ).…”
Section: Discussionmentioning
confidence: 99%
“…However, such a theory that either too much or too little of Nrf2 can lead to pathological endpoints cannot explain Nrf2-mediated cardiac phenotypes ( Zang et al, 2020a ). For example, CR-Nrf2 Tg mice is perfectly normal under physiological conditions, and sustained PO does not result in super-activation of Nrf2 in the heart although Nrf2 activation promotes the PO-induced cardiomyopathy ( Zang et al, 2020a ). In the present study, we showed that cardiac specific autophagy inhibition via CR-Atg5KO wiped out Nrf2-mediated cardiac protection while turning on Nrf2-mediated pathological cardiac remodeling and dysfunction, providing direct evidence to demonstrate a critical role autophagy in the control of Nrf2-mediated dichotomy in PO hearts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…But can hormesis by overdone? There is burgeoning evidence to suggest that persistent unsolicited Nrf2 overactivation, particularly alongside dysregulated autophagy, can progress cardiac disease despite being initially beneficial for resisting myocardial damage [ 57 ]. Thus, a molecular “tipping-point” clearly exists, which is dependent upon the pathological environment and the proper function and/or amenability to modulation of the downstream cytoprotective events that are governed by Nrf2 (i.e.…”
Section: Ros and Skeletal Muscle: Friend Or Foe?mentioning
confidence: 99%